Comparative Study of Quality Assurance Practices in Unity Schools and Private Secondary Schools in Kwara And Oyo States, Nigeria - Atanda, Olatunde; Olaifa, Sunday Adeseko (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This paper compared the quality assurance practices in Unity and private secondary schools in Kwara and Oyo States, Nigeria touching variables such as infrastructural facilities, staff discipline. The research design employed for the study was a descriptive survey type. The population of the study was made up of all Unity and Privates secondary schools in Kwara and Oyo States, Nigeria. Purposive and random sampling techniques were used to select the respondents in all the sampled schools. The data for the study were gathered through the use of questionnaires tagged â€œQuality Assurance Practices Questionnaireâ€ (QAPQ) administered to teachers, Vice Principals and Principals. The data gathered during this study were analyzed with inferential statistics called t-test and ANOVA. The findings revealed a slight difference in infrastructural facilities in the sampled schools. Private secondary schools in Kwara and Oyo State were rated higher than the Federal Government Colleges. This paper further revealed that the discipline and control of staff in private secondary schools in Kwara and Oyo States were stricter than the Federal Government Colleges in both States. Based on these findings, the paper recommended among others that there should be adequate provision of infrastructural facilities, efficient supervision of schools to maintain a quality standard of equipment, especially the provision of potable water and electricity in the Federal Government Colleges. Also, staff discipline in private secondary schools should be more relaxed instead of instant judgment in the interest of fairness and low staff turnover.